2008
DOI: 10.1021/jp0764384
|View full text |Cite
|
Sign up to set email alerts
|

Treating Entropy and Conformational Changes in Implicit Solvent Simulations of Small Molecules

Abstract: Implicit solvent models are increasingly popular for estimating aqueous solvation (hydration) free energies in molecular simulations and other applications. In many cases, parameters for these models are derived to reproduce experimental values for small molecule hydration free energies. Often, these hydration free energies are computed for a single solute conformation, neglecting solute conformational changes upon solvation. Here, we incorporate these effects using alchemical free energy methods. We find sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(199 citation statements)
references
References 60 publications
7
192
0
Order By: Relevance
“…32 Because of the large difference in dipole moments, the Poisson-Boltzmann equation predicts a difference of 4.6 kcal/mol between the two hydration free energies. 29 Given the large experimental difference in dipole moment, why are the hydration free energies so similar? Explicit solvent comes closer to reproducing the experimental difference.…”
Section: Real Solutes Also Appear To Have Hydration Free Energy Asymmmentioning
confidence: 99%
“…32 Because of the large difference in dipole moments, the Poisson-Boltzmann equation predicts a difference of 4.6 kcal/mol between the two hydration free energies. 29 Given the large experimental difference in dipole moment, why are the hydration free energies so similar? Explicit solvent comes closer to reproducing the experimental difference.…”
Section: Real Solutes Also Appear To Have Hydration Free Energy Asymmmentioning
confidence: 99%
“…This might be a problem when comparing with experimental data for flexible molecules [71], but not for the drug-like molecules, for which no such comparison is made. The conformations used were either taken from crystal structures of proteins with the ligand of interest [69,70,72,73] or from the most stable conformation, according to a systematic conformational search at the MMFF94 level with the Spartan software [74].…”
Section: Moleculesmentioning
confidence: 99%
“…As an example, one may look at human red blood cells (erythrocytes), one of the most widely studied cells in nature, and point to [32] for the value E 0 = −8.4 mV, as well as [33,34] for d = 78Å. However, the value of κ for a membrane is highly contentious, due to the fact that it depends sensitively upon a large variety of biophysical attributes of the membrane, such as hydration [35], pH value [36], and structural stability [37]. In a recent review, it was reported that the value of κ in literature ranges from 1 to 40 [38].…”
Section: Discussionmentioning
confidence: 99%